Upaya Guru PAI dalam Pembentukan Akhlakul Karimah pada Siswa - Sunardi, Sunardi; Kholik, Chasan Khairul; Mujahidin, Mujahidin (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
The formation of the akhlakul karimah in students is a very important aspect in Islamic religion education (PAI). PAI teacher has a central role in guiding students to a noble akhlak, in accordance with the teachings of Islam. This research aims to find out the efforts made by PAI teachers in the formation of karimah achlakul in students. In this research, the method used is a qualitative approach with case studies as research design. Data is collected in several ways, including in-person observations, interviews with PAI teachers, as well as analysis of PAI curriculum-related documents and PAI learning materials. The strategy includes direct teaching of Islamic values, giving examples in everyday life, as well as accustoming positive behavior through extracurricular activities. PAI teachers also use a holistic approach, which combines aspects of knowledge, attitudes, and practice in an effort to shape a charitable attitude in students